HUBUNGAN RIWAYAT KURETASE DAN OPERASI SECTIO CAESAREA DENGAN KEJADIAN PLASENTA REVIA DI RSUD KOTA PRABUMULIH - Gustika Anggriani (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
Placenta Previa is Abnormalities during pregnancy are characterized by the presence of placental tissue covering the cervix. Determine the history of curettage and sectio caesarea surgery the occurrence of placenta previa. method analytic, using a cross sectional approach. The population of this study were all mothers giving birth in the midwifery room at the Prabumulih City. General Hospital, which were 1778 people. This study using a random sampling technique as many as 326 respondents. The research instrument is a checklist. univariate analysis showed that from 326 respondents there were 123 respondents (37.7%) who had placenta previa and 203 respondents (62.3%) who did not experience placenta previa. there were 80 respondents (24.5%) who had a history of curettage and 246 people (75.5%) who did not have a history of curettage. there were 64 respondents (19.6%) who underwent cesarean section and 262 (80.4%) did not undergo cesarean section. Bivariate analysis it was found that of the 80 respondents who had a history of curettage, 62 (19%) had placenta previa and of the 61 respondents who did not have a history of curettage, 61 (18.7%) had placenta previa, from 63 respondents who had surgery. sectio caesarea there are 47 people (14.4%) experienced placenta previa and of 303 respondents who underwent sectio caesarea surgery there were 76 people (23.3%) experienced placenta previa. 0.000 < 0.05, there is a significant relationship between cesarean section surgery and placenta previa with a P value of 0.000 < 0.05. Keywords: Placenta previa, history of curettage, sectio caesarea operasi